Regime shifts, resilience and recovery of a cod stock - Lindegren, Martin; Diekmann, Rabea; Möllmann, Christian (Marine Ecology Progress Series, 2010)
ABSTRACT: In the North and Baltic seas Atlantic cod Gadus morhua stocks collapsed as part or one of the major factors inducing large-scale ecosystem regime shifts. Determining the relative contribution of overfishing and climate variability in causing these shifts has proven difficult. While facing similar climatic conditions, the Sound (i.e. a narrow strait located between the North and Baltic seas) differs from its neighbouring areas in the magnitude of fishing pressure as it is subjected to a local trawl fishing ban since 1932. By means of 3 independent multivariate analyses, we investigated the state and development of the Sound ecosystem, specifically testing for the occurrence of regime shifts and their potential drivers. By comparing the ecosystem development of the Sound with the neighbouring North and Baltic seas, we were able to demonstrate the positive effect of the trawl fishing ban on the resilience of the local cod stock to environmental change. The recovery and healthy condition of the Sound cod stock illustrate the need for adaptive marine management strategies that maximize ecosystem resilience.